FACTOR INFLUENCING OF PROFITABILITY: A CASE OF TEXTILE AND GARMENT COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Putra Ritonga, Mirwansyah; Ermal M, Eky; Hasibuan, Mhd Zulkifli (Accounting and Business Journal, 2020)
This study aims to determine whether there is an influence between Current Ratio and Debt to Asset Ratio on Return on Assets in Textile and Garment Companies listed on the Indonesia Stock Exchange. The methodological approach used in this research is associative research. The data analysis techniques, such as a classical assumption test, correlation, t-test, F-test, and the coefficient of determination. Using secondary data, this study obtained from textile and garment companies listed on the Indonesia Stock Exchange, while the samples as the purposive criteria were 8 textile and garment companies from 2008 to 2011. The results showed that the t-test value on Current Ratio and Debt to Asset Ratio are partially significant, also the F test results in the study showed positive results. Based on the coefficient of determination test results, the value of R square in the regression model leads to strong results. It can be seen that Current Ratio and Debt to Asset Ratio have a significant effect on Return on Assets partially or simultaneously.